KARIES GIGI DAN TOOTH LOST INDEX (TLI) PADA IBU MAJELIS TAKLIM PERKOTAAN - Eka Anggreni; Rikawarastuti Rikawarastuti (Jurnal Kesehatan Manarang, 2016)
WHO expects to achieve maximum functionality teeth population aged 35-44 years must be at least 20 teeth were still there. Lost Tooth Index (TLI) means the percentage of the number of permanent teeth were missing against the number of dental caries (DMF-T). This study aimed to describe TLI urban woman. The research method cross-sectional study in a population of women majelis taklim in the Village Cilandak Barat, South Jakarta. Samples are 30 people who obtained purposively. The data used are primary data through questionnaires to determine the characteristic of respondents (age) and intraoral examination to obtain the data of experience permanent dental caries (DMF-T) and TLI. The results showed urban women aged 35 – 44 years experience 1 – 2 lost teeth, while the age of 45 – 54 years ≥ 5 tooth loss. The average missing 4.83 with numbers DMF-T on average 6.66 so that the figure of 72.52% TLI. Urban women suffered a loss of 72.52% due to dental caries. Suggested respondents maintain dental and oral hygiene to reduce the risk of missing teeth due to caries and for mothers who have lost teeth using dental prostheses.